STATUS OF INFESTATION AND BIOLOGY OF PEPPER FRUIT FLY, ATHERIGONA ORIENTALIS (SCHINER) (DIPTERA: MUSCIDAE) - Herawani, Febrina; Rauf, Aunu; Santoso, Sugeng (Universitas Lampung, 2019)
Status of Infestation and Biology of Pepper Fruit Fly, Atherigona orientalis (Schiner) (Diptera: Muscidae). Numerous muscid flies Atherigona orientalis (Schiner) (Diptera: Muscidae) emerged from fruitfly-infested pepper fruits. It is not known whether A. orientalis is primary or secondary pest, and its biology is poorly studied. Research was conducted with the objectives to determine the status of infestation of A. orientalis on pepper fruits, and to study its biology. Field survey was conducted in pepper fields in Bogor, whereas study on its biology was done in laboratory. Field surveys showed that flies emerged from fruitfly-infested fruits consisted of 86.1% A. orientalis, 4.8% Bactrocera dorsalis, and 9.1% other fly species. Fruits having only A. orientalis representing 79.7% of the infested fruits. Number of A. orientalis flies emerged per fruit ranged 1-24, with an average of 3.5 individuals. Laboratory study showed incubation period of eggs was 1.62 d, larva development lasted 11.93 d, and pupa 5.08 d. Longevity of female adult was 32.85 d and male 31.40 d. Number of eggs laid by a single female ranged 12-191, with an average of 83.80. Net reproductive rate R0 =36.052, intrinsic rate of increase rm = 0.136, mean generation time T = 26.482, doubling time Dt = 5.098, and finite rate of increase ? = 1.145. Overall, our research indicated that A. orientalis was a primary pest of pepper fruits, with a high potential of population increase.